2016
DOI: 10.30597/mkmi.v9i1.439
|View full text |Cite
|
Sign up to set email alerts
|

Permintaan (Demand) Masyarakat Terhadap Pemanfaatan Asuransi Kesehatan Di Pt. Asuransi Jiwa Inhealth Makassar

Abstract: Salah satu indikator pengembangan sistem asuransi kesehatan adalah jumlah atau proporsi tenaga kerja yang bekerja di sektor formal. Makassar mempunyai porsi tenaga kerja sektor formal yang cukup tinggi, yaitu di atas 70% dari semua tenaga kerja. Namun, cakupan atau kepesertaan masyarakat terhadap berbagai jaminan kesehatan masih sangat rendah, masyarakat (tenaga kerja) yang tercakup jaminan pembiayaan kesehatan hanya 11,35% yang sebagian besar tercakup dalam askes, kartu sehat, Jamsostek dan askes lain. Peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…The poorer, middle, richer, and richest wealth quintiles were less likely to have health insurance than poorest� The previous study stated that there was no significant association between wealth quintile and health insurance� � 41 Another study stated that the richest households were more likely to have health insurance� � 36,42,43 This could have occurred because the health insurance scheme in Indonesia is different from that of other countries� The poorest populations receive subsidized insurance to maintain and increase their health status, , 44 such as payment for health services in the emergency department, , 45 treatment for chronic illness, , 46 and treatment of the factors associated with the success of diabetes mellitus management� � 47 The poorest population's health insurance is fully paid for by the government� The other schemes are paid for by the health insurance members themselves� This scheme makes the poorest populations more likely to be listed as health insurance member, making their coverage rate higher� The ownership of private health insurance may be the reason why the wealthier are less likely to have national health insurance� A study showed that the amount of monthly income as part of wealth is related to the demand for private insurance in Indonesia� � 48 To increase the coverage of health insurance for other economic groups, the government can subsidize premiums for them� The government can work with companies to pass regulations stating that each company has an obligation to pay for insurance for its workers� This regulation can also protect the health of workers� Rural households are less likely to have health insurance� � 40,43 The primary factor determining coverage for both the subsidized and contributory schemes in Indonesia is that citizens work and are urban residents of Java or Bali� � 49 The affordability of travel to the health insurance office can be another reason for low coverage� The existence of branch offices in each city can increase the reach of insurance agencies� An increase in the number of insurance agencies can make it easier for potential participants to register for NHI� The government can support the spreading of branch offices by providing good infrastructure and communication networks like telephone and internet� The role of the government in providing infrastructure greatly affects the existence of branch offices and customer service� Those who are divorced are less likely to have health insurance� Women often lose their health insurance in the months after a divorce 50 and thus become uninsured� � 51 Divorced women are more likely to experience socioeconomic disadvantages than married women� � 52 Divorced women lose their benefits in terms of health insurance as they are dropped from their husbands' health insurance policies� They also lose their dependent payments and are unable to afford other forms of coverage� Jobless divorced woman find it difficult to pay monthly insurance premiums, so they decide to d...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poorer, middle, richer, and richest wealth quintiles were less likely to have health insurance than poorest� The previous study stated that there was no significant association between wealth quintile and health insurance� � 41 Another study stated that the richest households were more likely to have health insurance� � 36,42,43 This could have occurred because the health insurance scheme in Indonesia is different from that of other countries� The poorest populations receive subsidized insurance to maintain and increase their health status, , 44 such as payment for health services in the emergency department, , 45 treatment for chronic illness, , 46 and treatment of the factors associated with the success of diabetes mellitus management� � 47 The poorest population's health insurance is fully paid for by the government� The other schemes are paid for by the health insurance members themselves� This scheme makes the poorest populations more likely to be listed as health insurance member, making their coverage rate higher� The ownership of private health insurance may be the reason why the wealthier are less likely to have national health insurance� A study showed that the amount of monthly income as part of wealth is related to the demand for private insurance in Indonesia� � 48 To increase the coverage of health insurance for other economic groups, the government can subsidize premiums for them� The government can work with companies to pass regulations stating that each company has an obligation to pay for insurance for its workers� This regulation can also protect the health of workers� Rural households are less likely to have health insurance� � 40,43 The primary factor determining coverage for both the subsidized and contributory schemes in Indonesia is that citizens work and are urban residents of Java or Bali� � 49 The affordability of travel to the health insurance office can be another reason for low coverage� The existence of branch offices in each city can increase the reach of insurance agencies� An increase in the number of insurance agencies can make it easier for potential participants to register for NHI� The government can support the spreading of branch offices by providing good infrastructure and communication networks like telephone and internet� The role of the government in providing infrastructure greatly affects the existence of branch offices and customer service� Those who are divorced are less likely to have health insurance� Women often lose their health insurance in the months after a divorce 50 and thus become uninsured� � 51 Divorced women are more likely to experience socioeconomic disadvantages than married women� � 52 Divorced women lose their benefits in terms of health insurance as they are dropped from their husbands' health insurance policies� They also lose their dependent payments and are unable to afford other forms of coverage� Jobless divorced woman find it difficult to pay monthly insurance premiums, so they decide to d...…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the amount of monthly income as part of wealth is related to the demand for private insurance in Indonesia. 48 To increase the coverage of health insurance for other economic groups, the government can subsidize premiums for them. The government can work with companies to pass regulations stating that each company has an obligation to pay for insurance for its workers.…”
Section: Discussionmentioning
confidence: 99%
“…Tingkat pendapatan adalah sejumlah nilai yang diperoleh dari usaha, kerja, atau imbalan dari hasil usaha yang biasanya dapat diukur pada tingkatan tertentu. 9 Berdasarkan data kuesioner yang diperoleh untuk variabel pendapatan dengan kepatuhan membayar iuran BPJS dari total 111 sebanyak 76 (77.1%) yang memiliki pendapatan cukup dan patuh dalam membayar iuran dan sebanyak 15 (13.9%) yang berpendapatan cukup tetapi kurang patuh. Dari hasil tersebut dapat dilihat responden yang berpendapatan kurang dan patuh membayar iuran sebanyak 18 (16.9%) sedangkan responden yang memiliki pendapatan kurang tetapi kurang patuh membayar iuran BPJS mandiri sebanyak 2 (3.1%).…”
Section: Hubungan Antara Variabel Pendapatan Dengan Kepatuhan Pasienunclassified
“…In modern times, every individual has the right to live a healthy and prosperous life and get the right to food, clothing, health services and health insurance (Oldistra & Machdum, 2020). But unfortunately, not everyone realizes how important health is even though no one knows when calamities and illnesses will come that require large costs (Ashari, 2015), plus we never know whether our finances will always be available when we need them. Therefore, there is a solution called "Health Insurance" which based on its membership is divided into two, namely compulsory health insurance and voluntary health insurance and aims to ensure comprehensive health financing.…”
Section: Introductionmentioning
confidence: 99%